The Evolution of Women in Middle Eastern Politics: Opportunities for Women in Parliament - Akande, Abdul-Rahman (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: All across the globe women are assuming roles that were previously reserved for their male counterparts be it at the lowest or highest echelon of political power. Unlike the rest of the world, the Middle East and Muslim world have been slow to come to terms with this changing reality, but they too are gradually succumbing to the changing culture of increased women s participation in politics. Various countries in different continents have benefited from the increased participation of women in politics and it may be argued that similar successes could also be replicated in the political arena of this part of the world. Lebanon, as an illustration, presents a mid-way position in the region in that it is more liberal and has a more advanced civil society, but women are yet to seriously penetrate politics. In the larger context of low women s political participation globally, the Middle East suffers from even lower penetration of women in politics. As a medium towards development and international integration, women present a somewhat untapped resource in the social, economic and political arenas in the region, and this study aims to provide information and recommendations to show opportunities for increasing their political participation, particularly at the parliamentary level of government. If the acknowledged political accomplishments of women in other countries are anything to go by, particularly post-conflict societies, the increased involvement of women in Middle East politics will benefit the region through better governance that would permeate other aspects of society. Thus, the argument being made here that women s political participation in the Middle East and Muslim countries cannot be achieved without the reassessment and implementation of the specified recommendations revising education, establishing quota systems and institutionalizing regional reform.